A latent class analysis on students' beliefs about teachers' practices enhancing their well-being - Gaitas, Sérgio; Silva, José Castro; Poças, António (Frontiers in Education, 2024)
Student well-being and student voice are two interrelated concepts that can play a critical role in education. While Student well-being refers to the overall state of students' physical, mental, and emotional health, student voice represents the active involvement and participation of students in shaping their own educational experiences. Notwithstanding the intimate association, there is a limited body of research that explores how students' distinct perceptions of teachers' practices that promote their well-being influence students' actual well-being levels. To address this research gap, a study was conducted involving 486 students. The participants, with an average age of 13.5 years, completed a questionnaire. Among the participants, 51.1% identified as female, and 13.6% had experienced academic retention. The latent class results classified the 7–9 grade student's beliefs about teacher's practices into “few times,” sometimes' and “often.” The model fitting results were as follows: Akaike Information Criterion (AIC) was 2,555.904, Bayesian Information Criterion (BIC) was 2,610.244, Adjusted Bayesian Information Criterion (aBIC) was 2,568.983, and Entropy was 0.802. Compared with the “few times” and “sometimes” class, the “often” class was more prevalent in 8th grade (p = 0.05) and among male students (p = 0.04). Findings show that class membership is a predictor of student well-being (interpersonal, life satisfaction and perceived competence). Students who feel that their teachers are attentive, supportive, and address their needs more frequently are more likely to experience enhanced well-being.